Varnished without a trace - Simon, Misty (Simon, Misty. Tallie Graver mystery., 2020)
"This Christmas, Tallie Graver would like to take a break from running her cleaning business to be with her boyfriend, Max, and enjoy their first holiday together--alone. Instead, she's stuck keeping her mother and grandmother from duking it out during the town's annual Christmas Eve bingo game. As for festive spirit, she'll have to settle for her mean-spirited Aunt Ronda, whose mouth could use some soap. The night only gets worse after Tallie discovers Ronda's body. It seems someone cleaned her clock with a can of varnish. While all the evidence points to Ronda's husband, Tallie doesn't believe her beloved Uncle Hoagie could do such a dirty deed. Of course, his sudden disappearance doesn't help his case. If Tallie hopes to clear his name, she'll need to dig up some dirt to locate the real killer. Otherwise, someone else could get rubbed out . . ." --